Antibiotic resistance among patients with urinary tract infections in Kandahar, Afghanistan - Bilal A Rahimi; Jalat K Afghan; Rahmatullah Sirat; Khalil A Kakar; Wais M Lali; Najeebullah Rahimy; Khushhal Farooqi (Wolters Kluwer Medknow Publications, 2023)
Background: Antimicrobial resistance is a global public health threat. Highest burden of resistance is reported from low- and middle-income countries. Objectives: To investigate and report the current scenario of increased antibiotic resistance of uropathogens among symptomatic urinary tract infection patients in Kandahar, Afghanistan. Methods: From January 2018 to December 2021, this retrospective study was carried out at two main hospitals in Kandahar City, Afghanistan. Here, culture and sensitivity profiles of uropathogens were studied among symptomatic Bacteriuria in the presence of genitourinary symptoms (i.e., dysuria, suprapubic pain or tenderness, frequency, or urgency) (UTI) patients. Results: Among urine samples of 1589 patients, 1047 (65.9%) were culture positive and included in this study. Most of these patients (626/1047 [59.8%]) were females, with majority (818 [78.1%]) having age between 19 and 39 years. Gram-negative bacteria were the most prevalent (840/1047 [80.2%]), with E. coli (653/1047 [62.4%]) as the most common isolated uropathogen. Overall gram-negative bacteria had higher resistance against commonly used antibiotics of cotrimoxazole (62.8%), ciprofloxacin (56.0%), levofloxacin (47.5%), cefixime (44.5%), fosfomycin (41.5%), and even ceftriaxone (48.3%). Conclusions: Kandahar province has higher resistance rates against commonly used empirical antibiotics like norfloxacin, ciprofloxacin, levofloxacin, and cefixime. Nitrofurantoin should be used as the first-line antibiotic in treating UTI patients. Public health authorities should make strict regulations and policies to reduce irrational use, inappropriate prescription, and over-the-counter availability of antibiotics in Kandahar.